MEMILIH PEMIMPIN DALAM PRAKTIK KEPEMIMPINAN ORGANISASI SEKOLAH DI ERA GLOBAL - Sunarta sunarta (Universitas Negeri Yogyakarta, 2013)
The leader and leadership courses have produced many hypotheses which haven’t been solved from time to time. With regard to the demands of the globalization era recently, the successful organizations are those which are ruled by figures who have comparative and competitiveness strengths in many fields. In educational context, a leadership can be seen from the practice of school management starting from the basic educational level to the higher one. Educational leadership in the practice of school management expects that the one who plays roles and mandated as a leader must have specific requirements of a leader. Social life in the globalization era has changed the mindsets and views of the people in the world at any level. This influences the awareness of striking for their personal and social rights in the organization. A leader is someone or subject that leads as leadership manifestation such as authority, responsibility, commands, and delegation to the subordinates in an organization. Meanwhile a leadership is an art of persuading, directing people through obedience, belief, respect, and cooperation based on enthusiasm to meet the goals, A Dale Timpe, (1987). In order to give influence to the development of the organization, there are four leadership aspects that should be developed, such as (1) follower, (2) situation (3) communication and (4) leader. Key words: leader, leadership, school organization, globalization era.